Empowerment and Modernization: Analysis of Public Management in a Local Government in Peru - Ingunza Nesterenko, Miguel Antonio (2024)
Objective. The main objective of this research is to understand the extent to which human resource empowerment influences the modernization framework of Public Administration in the Provincial Municipality of Ambo, taking into consideration fundamental aspects such as the characteristics and principles of empowerment. Methods. The research is applied and of a descriptive correlational level. Data collection techniques included documentary analysis and content analysis. The analysis procedure was conducted through critical reasoning. Results. The article presents results supporting the overall hypothesis, indicating a moderate positive correlation (r=0,422) between Empowerment and Modernization in the Public Management of the Provincial Municipality of Ambo in 2019. Conclusion. It is concluded that empowerment, by empowering employees for decision-making, promotes smooth communication and shared leadership.